Role of Antioxidant Supplements in Idiopathic Male Infertility in Erbil City - Chro Yaseen Qader; Tarq Aziz Toma; Sizar Sherzad Rasool; Kawa Fareq Dizaye (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: Fertil Aid for Men is a non-prescription dietary supplement, it’s a mixture of multiple antioxidants,vitamins, a blend of herbal ingredients, and amino acid, as L-Carnitine. This research aims to appraise theeffectiveness of a mixture of vitamins and antioxidants on seminal fluid parameters in males with idiopathicinfertility.Method: Thirty-three men with idiopathic infertility were involved inthis prospective clinical study. The baselinesemen specimens were taken from the subjects following three to seven days’ abstinence. Semen parametersincluding (volume, pH, concentration, and motility) were measured. Abnormal sperm sample subjects were givena FertilAid capsule three times daily for 90 days then final semen analysis was estimated.The outcomes of this study demonstrated consumption of fertilAid has significantly improved sperm count/ml (p< 0.05), also significant amelioration in the sperm motility including progressive and non-progressive motility (p< 0.05). The rate of total sperm motility was significantly improved (p < 0.05).The concentration of immotile spermhas considerablyreduced (p < 0.05).Conclusion: The administration of a combination of L-Carnitine, Zinc, Maca Root, Asian Ginseng, Vitamin C, E,Beta Carotene, and Selenium PLUS CoQ10 in idiopathic male infertility has notably improved sperm parameters.